Unprescribed and unnoticed: Retrospective chart review of adverse events of interactions between antidepressants and over-the-counter drugs - Woroń, Jarosław; Chrobak, Adrian Andrzej; Ślęzak, Daniel; Siwek, Marcin (Frontiers in Pharmacology, 2022)
Aim: To systematically evaluate prevalence and clinical characteristics of adverse effects of antidepressants and OTC drugs interactions in a retrospective chart review. Methodology: Dataset of 1145 registered adverse events were evaluated. Reports were selected for further analysis if pharmacoepidemiological avaluation indicated the presence of high probability of a causal relationship between antidepressants and OTC interaction and the occurrence of side effect. Following variables were extracted from the records: sex, age, medical comorbidities, antidepressant and other concomitant medications, clinical consequences ant the possible interaction mechanisms. Results. 368 showed causal relationship with the simultaneous use of antidepressant with another drug. 15 adverse events (4%) were related to the use of OTC medicine, particularly omeprazole, diphenhydramine, Japanese ginkgo biloba, ibuprofen, diclofenac and sildenafil. All of the analysed side effects were categorized as the result of pharmacokinetic interactions. Here we report identified OTC drugs with corresponding antidepressants and clinical manifestations of DDI. Omeprazole: agomelatine (nausea, abnormal dreams), fluoxetine (extrapyramidal symptoms, paresthesias), sertraline (vertigo, yawning), escitalopram (oral vesiculation). Diphenhydramine: sertraline (diaphoresis, insomnia, vertigo), paroxetine (pruritus, headache), duloxetine (oropharyngeal pain). Japanese ginkgo biloba: citalopram (bradycardia), trazodone (vertigo, taste pervesion), mianserine (restless legs syndrome). Diclofenac: escitalopram (oral vesiculation), and fluoxetine (restless legs syndrome). Ibuprofen: agomelatine (anxiety and nausea), sertraline and omeprazole (QTc prolongation). Sildenafil: fluoxetine (genital oedema) and sertraline (myocardial infarction). Conclusions: The use of OTC drugs by the patients should be monitored. Pharmacokinetic interactions between nonprescribed medicines and antidepressants may increase concentration and severity of side effects of latter ones.